Effect of the Shape of Steel Fibers on Drying Shrinkage of Concrete - Lamen Sryh; Nurdeen Altwair; Muftah Sreh (African Journal of Advanced Pure and Applied Sciences, 2024)
This paper presents the experimental results of tests that were conducted to consider the effect of the shape of steel fibers on the drying shrinkage strains of concrete. Three different types of steel fibers differing in their shape (straight, hooked-end and crimped) and aspect ratios (l/d= 45, 65 and 80) were added to the concrete mixes with a volume content of (Vf= 1%). The main objective of this investigation was to clarify how the shape and aspect ratio of steel fibers can restrain the shrinkage strains of the concrete. Small prisms (75×75×200mm) were cast for six different concrete mixes and cured for 28 days, after which they were tested for up to 90 days. In general, the results showed that there were considerable reductions in drying shrinkage strains when the steel fibers were added to the concrete. The addition of crimped steel fibers led to the greatest decrease in shrinkage strain, by 22%, and the straight type recorded the lowest decrease 10%, in comparison with the plain concrete. In terms of the aspect ratio, it was observed that with increased diameters of the steel fibers, which decreased the aspect ratio, the strain caused by drying shrinkage was reduced.